Amyloidogenic Intrinsically Disordered Proteins: New Insights into Their Self-Assembly and Their Interaction with Membranes - Scollo, Federica; La Rosa, Carmelo (Life (Basel, Switzerland), 2020)
Aβ, IAPP, α-synuclein, and prion proteins belong to the amyloidogenic intrinsically disordered proteins' family; indeed, they lack well defined secondary and tertiary structures. It is generally acknowledged that they are involved, respectively, in Alzheimer's, Type II Diabetes Mellitus, Parkinson's, and Creutzfeldt-Jakob's diseases. The molecular mechanism of toxicity is under intense debate, as many hypotheses concerning the involvement of the amyloid and the toxic oligomers have been proposed. However, the main role is represented by the interplay of protein and the cell membrane. Thus, the understanding of the interaction mechanism at the molecular level is crucial to shed light on the dynamics driving this phenomenon. There are plenty of factors influencing the interaction as mentioned above, however, the overall view is made trickier by the apparent irreproducibility and inconsistency of the data reported in the literature. Here, we contextualized this topic in a historical, and even more importantly, in a future perspective. We introduce two novel insights: the chemical equilibrium, always established in the aqueous phase between the free and the membrane phospholipids, as mediators of protein-transport into the core of the bilayer, and the symmetry-breaking of oligomeric aggregates forming an alternating array of partially ordered and disordered monomers.
Keywords: membrane; CMC; protein-transport; amyloids; lipids; intrinsically disordered proteins; lipid; toxicity; lipid-assisted protein transport; symmetry-breaking